2021
DOI: 10.1186/s12933-021-01388-2
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of liver fibrosis and steatosis by transient elastography for cardiovascular and mortality outcomes in individuals with nonalcoholic fatty liver disease and type 2 diabetes: the Rio de Janeiro Cohort Study

Abstract: Background Liver stiffness measurement (LSM, which reflects fibrosis) and controlled attenuation parameter (CAP, which reflects steatosis), two parameters derived from hepatic transient elastography (TE), have scarcely been evaluated as predictors of cardiovascular complications and mortality in individuals with type 2 diabetes and nonalcoholic fatty liver disease (NAFLD). Methods Four hundred type 2 diabetic patients with NAFLD had TE examination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 38 publications
(59 reference statements)
5
22
0
Order By: Relevance
“…Moreover, low body weight and thus (assumed) low liver fat as well as ALT values in the lower normal range were previously reported to associate with worse cardiovascular outcomes and mortality 30 . Of interest, advanced liver fibrosis (as measured by transient elastography) was identified as a risk marker and severe steatosis as a protective factor for cardiovascular complications and mortality in individuals with type 2 diabetes and NAFLD, which would support the present results 31 …”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Moreover, low body weight and thus (assumed) low liver fat as well as ALT values in the lower normal range were previously reported to associate with worse cardiovascular outcomes and mortality 30 . Of interest, advanced liver fibrosis (as measured by transient elastography) was identified as a risk marker and severe steatosis as a protective factor for cardiovascular complications and mortality in individuals with type 2 diabetes and NAFLD, which would support the present results 31 …”
Section: Discussionsupporting
confidence: 87%
“…30 Of interest, advanced liver fibrosis (as measured by transient elastography) was identified as a risk marker and severe steatosis as a protective factor for cardiovascular complications and mortality in individuals with type 2 diabetes and NAFLD, which would support the present results. 31 The present analysis further suggests that study participants in all steatosis and fibrosis risk categories profit similarly in relative terms from empagliflozin treatment in regard to cardiorenal outcome and all-cause mortality. Similarly, former analyses of the EMPA-REG OUT-COME study reported that cardiorenal treatment benefits with empagliflozin are consistent across age groups as well as underlying cardiovascular and heart failure risk.…”
Section: Discussionsupporting
confidence: 60%
“…Regarding the increased risk of CVD-related mortality, a recent study consistently revealed that advanced hepatic fibrosis was significantly associated with the risks of CVD events and mortality [ 36 ]. Advanced liver fibrosis, measured by hepatic transient elastography, was a risk marker while severe steatosis was a protective factor for cardiovascular complications and mortality in individuals with type 2 diabetes and NAFLD [ 37 ]. Collectively, these results suggest that advanced hepatic fibrosis is potentially useful as a screening tool for predicting both hepatic and extrahepatic adverse outcomes in patients with type 2 diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…Within this category, TE is extensively available and can be used as a point-of-care test to estimate liver fibrosis by measuring liver stiffness and hepatic steatosis using controlled attenuation parameter (CAP) measurement [ 39 , 40 ]. The practice guidelines of the Brazilian Society of Hepatology and Brazilian College of Radiology have recently supported the use of elastography, among others, as a tool to assess fibrosis and steatosis in various chronic liver diseases, including NAFLD; due to its accuracy, elastography seems to be a non-invasive and cost-effective alternative to liver biopsy [ 41 ].…”
Section: Ultrasound-based Hepatic Shear Wave Elastographymentioning
confidence: 99%